Hyperkalemia due to hyporeninemic hypoaldosteronism with liver cirrhosis and hypertension. - Kee, C. S. (Korean Academy of Medical Sciences, 1993)
A 49-year-old man with liver cirrhosis and hypertension was found to have hyperkalemia out of a degree of renal insufficiency and metabolic acidosis with low to normal anion gap, aggravated by volume contraction with diarrhea and medications (captopril, spironolactone and atenolol) interfering with potassium homeostasis. Plasma renin activity and serum aldosterone levels of this patient on a regular diet after discontinuation of medications were very low compared to those of five other cirrhotic patients with normokalemia as controls. Also, the renin-aldosterone stimulation testing on this patient performed by sodium restricted diet and furosemide, upright position and by angiotensin converting enzyme inhibition (captopril, 50 mg) showed the blunted renin and aldosterone responses to each of these stimuli, almost no changes from baseline renin and aldosterone levels, it was concluded that the underlying defect responsible for hyperkalemia in this case was hyporeninemic hypoaldosteronism and this was aggravated by other factors or drugs affecting potassium homeostasis.